The food service industry in the Islamic City of Marawi prevailing conditions and services - Mambuay, Cecile B.
This study focused on the prevailing conditions and services of 52 selected foodservices in the Islamic City of Marawi. Data gathering was primarily through a questionnaire, reinforced by interviews. On-site observations and office visits were also made. Samples were drawn using random sampling with replacement. Analysis of data indicated the following: Most of the owners/operators were between 31-40 years old, married and Muslims. Male and female owners/operators almost equaled each other in number. Most had spent considerable number of years in school. Operating on single proprietorship, these foodservices are mostly managed by the owners themselves. Initial capital investment range from P20,000.00-P50,000.00. Averaging 1-3 years in the business, customers in these foodservices are mostly businessmen, employees and mosque goers. A number of them enjoyed an average daily gross sales of about P500.00 to P900.00 while their daily expenses averaged between P300.00-P699.00. Workers, usually between 1-5 in number in most of these foodservices, receive monthly wages from P200.00-P499.00. Majority operated seven days a week, usually opened at 6:00 a.m.-7:00 a.m. and closed at 7:00 p.m.-8:00 p.m. During Ramadan, the fasting month of Muslims, 71 percent of these establishments are closed. Those which opened reset their serving schedule to dusk until dawn. The following menu items were found to be popular in these foodservices: pizawanan a carabao, pizawanan a manok, and piyarun a manok; (meat dishes); tilapia, fried fish, and aruan (fish dishes); ampalaya with eggs, eggplant, and beans guisado (vegetable dishes); pancit canton, pancit behon, anf spagheti (pasta). For snacks, assorted cakes, breads and pancake were preferred. Being an Islamic City, no alcoholic beverages are sold in Marawi. Most owners/operators said patronage of their establishments was due to: price of food, good service, and taste of food. Likewise, for some practices done from menu planning to food service, peculiar to these foodservices were: the use of sumbali meat and the closure of business operations during the month of Ramadan. Modern technology has caught up in most foodservices as evidenced by their use of aluminum cooking utensils, gas stoves with liquefied petroleum gas (LPG) as fuel. Breakable serving and dining wares are used. Of the 52 foodservices studied, 49 were registered with the Mayor's Office, 22 with the City Health Office, and 9 with the Department of Trade and Industry. Four were accredited by the Department of Tourism. This can mean that not all foodservices are aware and/or mindful of their obligation to secure permits and licenses from the aforementioned government agencies. The foodservices identified the following problems: poor garbage waste disposal and drainage system, unscheduled disruption of water and power supply, poor credit collection, lack of skilled work force, increase in the prices of prime commodities, lack of capital, and lack of space for further expansion. In conclusion, the study revealed that some peculiarities exist in foodservices in Marawi City. These maybe be attributed to its distinct cultural setting. Culture always plays a significant role, even in the foodservice business.